2005
DOI: 10.1007/s00125-005-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in insulin sensitivity and secretion from birth to age three years in small- and appropriate-for-gestational-age children

Abstract: Aims/hypothesis: Insulin resistance and type 2 diabetes risk in human subjects who were small-for-gestationalage (SGA) at birth may be a consequence of rapid early postnatal weight gain. Materials and methods: We prospectively studied early changes in fasting insulin sensitivity and insulin secretion, assessed by a short intravenous glucose tolerance test that was conducted several times from birth to 3 years of age in 55 SGA (birthweight below fifth percentile) newborns and in 13 newborns with a birthweight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
178
4
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(196 citation statements)
references
References 28 publications
10
178
4
4
Order By: Relevance
“…Reduced insulin sensitivity in SGA born infants can already be demonstrated in early childhood (5,7). In the present study, we showed that at 1 y of age term born SGA children have a high prevalence of high triglycerides, with the cut-off value based on term born AGA children from the same population.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Reduced insulin sensitivity in SGA born infants can already be demonstrated in early childhood (5,7). In the present study, we showed that at 1 y of age term born SGA children have a high prevalence of high triglycerides, with the cut-off value based on term born AGA children from the same population.…”
Section: Discussionmentioning
confidence: 44%
“…This is based on the studies of Barker et al (1), who first indicated the importance of fetal growth for development of the metabolic syndrome in adulthood and showed an increasing prevalence with decreasing birth weight. Not only term smallfor-gestational-age (SGA) born infants, but also preterm born infants have an increased prevalence of several components of the metabolic syndrome, already in childhood (2)(3)(4)(5)(6)(7)(8)(9). The relation between metabolic syndrome components in childhood and fetal growth was studied by Jaddoe et al (10); they showed that first trimester fetal growth restriction is associated with an adverse cardiovascular risk profile at 6 y of age.…”
mentioning
confidence: 99%
“…However, it is a less satisfactory explanation for variation across the normative range and in any event insulin resistance does not develop until well after birth. 59 We 3 and Bateson 60 independently proposed an extension of this line of argument, suggesting that these relationships are responses to variation within the anticipated range of early developmental environments and involve the physiological processes of developmental plasticity rather than the pathological processes of developmental disruption. In particular, both of us proposed an anticipatory model based on the considerable comparative evidence that organisms in early development may make adaptive responses which are of no advantage at the time they are made but are able to better match the organism to the later predicted environment.…”
Section: The 'Mismatch' or 'Thrifty' Pathwaymentioning
confidence: 99%
“…More recently a study of small for gestational age infants (SGA) and appropriate for gestational age infants (AGA) showed increased insulin sensitivity at birth in (SGA) infants, which could potentially drive their rapid postnatal catch up growth. By 3 years of age (SGA) offspring were more insulin resistant than (AGA) offspring however (14).…”
Section: Page 5 Of 21mentioning
confidence: 99%